Inovasi Pembelajaran Guru SMP Negeri 1 Cimerak Pangandaran: Pemanfaatan Pelatihan Microsoft Office Specialist (MOS) di Era Industri 4.0 - Pantjawati, Arjuni Budi; Juanda, Enjang Akhmad; ardiansyah, Neris peri; Rizqulloh, Muhammad Adli; Nurhakim, Raihan (Jurnal Dharma Bhakti Ekuitas, 2024)
The industrial revolution has brought about inevitable changes in human life, and no sector is exempt from this transformation. Education, as the foundation for the future, faces immense pressure to adapt to technological advancements. In the context of the Industrial Revolution 4.0, the role of teachers becomes increasingly significant. To ensure that they possess the necessary qualifications, training initiatives like the Microsoft Office Specialist (MOS) PowerPoint are highly relevant. We, as part of our commitment to enhancing education in Pangandaran, have decided to hold a MOS PowerPoint training session specifically targeted at the teachers of SMPN 1 Cimerak. This is because the teachers at SMPN 1 Cimerak are not yet able to utilize all the features in the PowerPoint application. The approach we use in this training is based on the proven GOAD method. The first stage is the training needs assessment, where we collaborate with the teachers to understand the challenges they face. Based on these findings, we design a relevant and efficient training method. Our training materials are tailored to the needs of the teachers and the latest technological developments. Training sessions are held with enthusiasm and interactivity, allowing teachers to learn practically. After the training, we conduct a thorough evaluation to ensure proper understanding. If necessary, we update our training materials based on teacher feedback. This initiative is a crucial step in preparing educators to face the challenges of the present era. With MOS PowerPoint skills, teachers can be more effective in delivering lesson material and assist students in developing competencies relevant to the Industrial Revolution 4.0. The dedication carried out at SMPN 1 Cimerak Pangandaran went smoothly; the material presented was found to be interesting by the participants. Moreover, participants felt the presenter conveyed the material very well. Keywords: Microsoft Office Specialist, Goad Method, Power Point Abstrak Revolusi industri telah membawa perubahan tak terhindarkan dalam kehidupan manusia, dan tidak ada sektor yang terlepas dari transformasi ini. Pendidikan, sebagai fondasi masa depan, menghadapi tekanan besar untuk beradaptasi dengan perkembangan teknologi. Dalam konteks Revolusi Industri 4.0, peran guru menjadi semakin penting. Untuk memastikan bahwa mereka memiliki kualifikasi yang diperlukan, inisiatif pelatihan seperti Microsoft Office Specialist (MOS) PowerPoint sangat relevan. Kami, sebagai bagian dari komitmen kami terhadap peningkatan pendidikan di Pangandaran, telah memutuskan untuk mengadakan sesi pelatihan MOS PowerPoint yang khusus ditujukan untuk guru-guru SMPN 1 Cimerak. Hal ini dikarenakan guru-guru di SMPN 1 Cimerak belum mampu menggunakan semua fitur yang ada di applikas Power Point. Metoda pendekatan yang kami gunakan dalam pelatihan ini didasarkan pada pendekatan GOAD yang terbukti efektif. Tahap pertama adalah penilaian kebutuhan pelatihan, di mana kami bekerja sama dengan para guru untuk memahami tantangan yang mereka hadapi. Berdasarkan hasil ini, kami merancang metode pelatihan yang relevan dan efisien. Materi pelatihan kami dirancang sesuai dengan kebutuhan guru dan perkembangan teknologi terkini. Sesi pelatihan diadakan dengan penuh semangat dan interaktif, memungkinkan guru untuk belajar secara praktis. Setelah pelatihan, kami melakukan evaluasi mendalam untuk memastikan pemahaman yang tepat. Jika diperlukan, kami memperbarui materi pelatihan kami sesuai dengan umpan balik guru. Inisiatif ini merupakan langkah penting dalam mempersiapkan para pendidik untuk menghadapi tantangan zaman sekarang. Dengan keterampilan MOS PowerPoint, para guru dapat lebih efektif dalam menyampaikan materi pelajaran dan membantu siswa mengembangkan kompetensi yang relevan dengan Revolusi Industri 4.0. Pengabdian yang dilakukan di SMP Negeri 1 Cimerak Pangandaran berjalan dengan lancar, materi yang disampaikan dirasa menarik oleh para peserta, selain itu peserta merasa pemateri dapat menyampaikan materi dengan sangat baik. Kata kunci: Microsoft Office Specialist, Metode Goad, Power Point.